JENIS IKAN DI HULU SUNGAI OPAK KABUPATEN SLEMAN - , BRQ DIAS BAHARY A., Dr. Ir. Djumanto, M. Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The occurance of fishes in river ecosystem is very important as biotic resource for community in surrounding water. The objective of this study was to investigate the fish species and their distribution in the upper part of Opak Basin. Sampling was done in five stations with a distance between station around 3-4 km each. Fish sample was collected using a scoop net with netting around 100 m, then repeated every week. All samples were collected and preserved in 5 % formalin until identification in the laboratory. Environmental conditions was measured in each station of sampling namely velocity, temperature, pH, depth, width, the base substrate and vegetation surrounding waters. The results showed that there were 13 species in 8 families and 3 order found among stations. The most abundance was Poecilia sp. followed by Channa striata, Nemacheilus fasciatus, Nemacheilus sp., Oreochromis niloticus, Oreochromis sp., Puntius binotatus, Rasbora argyotaenia, Lepidocephalychthys haseltii, Cyprinus carpio, Dermogenys pusilla, Xiphophorus variatus, Ryacichthys aspro. Guppy (Poecilia sp.) was the most abundant species and occured in almost all observations. Water velocities range from 0.3 to 0.55 m/s